An uncommon or just an ecologically demanding species? Finding of aggregations of the brittle-star Ophiothrix maculata on the Northwest African slope. (January 2018) - Calero, Belén; Ramos, Ana; Ramil, Fran
Abstract: Ophiuroidea constitutes the largest class of the phylum Echinodermata. It includes families with suspension-feeder behaviour that can be found in dense aggregations in all oceans worldwide. Ophiothrix maculata was known as a rare suspension-feeder brittle star, with only four records in the Eastern Central Atlantic dating from almost 100 years ago. During the ten multidisciplinary Spanish and Norwegian surveys carried out from 2004 to 2012 off Northwest Africa, between the Gibraltar Strait and the Sierra Leone border from 19 to 1888 m depth, we sampled 1298 stations. We gathered about one million individuals and 124 kg of brittle stars at 501 of the stations. Eight hundred and thirty-two specimens of Ophiothrix maculata were collected at six localities on the continental slope off Mauritania, Western Sahara and Guinea Bissau, at depths between 155 and 594 m. The Guinea Bissau samples represent the southernmost current record for the species. Even though Ophiothrix maculata has been previously recorded only in isolation, we discovered dense concentrations on the Mauritanian slope on the Wolof's Seamount (580 individuals) and off the Western Sahara, in a Lophelia pertusa reef (202 individuals). In this paper, we describe these findings and discuss the association of this species to hard-bottom habitats and high primary production areas, outside of the oxygen minimum zone (OMZ). We also analyse what other factors may explain the patchy distribution of O. maculata on the Northwest African slope. Highlights: An intense megabenthos-sampling programme was developed, between 2004 and 2012, along the Northwest African continental margin, from the Strait of Gibraltar to the northern border of Sierra Leone. The Northwest African region constitutes one of the most highly productive areas worldwide, linked to upwelling phenomena. Ophiothrix maculata is an uncommon species mainly restricted to Northwest African slope where it exhibits a patchy distribution. Dense aggregations of Ophiothrix maculata have been reported for the first time, in Northwest Africa. Where the two main concentrations were associated with hard-bottoms and suspension-feeder vulnerable habitats.